Estrategias de marketing en Comercial Sandrita del Cantón Alfredo Baquerizo Moreno Jujan. - Rodríguez Rodríguez, Angie Pamela (2024)
The case of Comercial Sandrita, located in the Alfredo Baquerizo Moreno Juján canton, is highly relevant for several reasons. This analysis not only provided us with information on specific practices, but also offered valuable lessons and knowledge applicable to the field of marketing in general. The main objective was to examine comercial Sandrita's marketing strategies to understand their impact on its positioning, performance, and competitiveness in the market. Based on a qualitative method, the research used interviews and data from the target market to formulate theoretical conclusions. The methodology focused on the variable of marketing strategy within the context of the commercial, applying techniques such as the SWOT matrix and interviews. The results indicated that Comercial Sandrita lacks an effective marketing strategy, which limits its competitiveness in a saturated market without clear differentiation. It also identified the absence of adequate training in the use of marketing tools. It was found that it has a solid base of strengths that it can capitalize on to take advantage of emerging opportunities in the market. It is highlighted that Comercial Sandrita has failed to create and execute effective strategies that could increase its visibility in the market. The investigation covered the areas of Financial Management, Administration, Taxation, Audit and Control, as well as Marketing and Commercialization, providing a comprehensive view of the situation and highlighting the need for a more solid marketing strategy.